Produção familiar e as estratégias de reprodução social no espaço rural do município de Indiana (SP) - Menegati, Regiane Aparecida [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
Este trabalho tem como objetivo analisar a dinâmica da produção familiar no Município de Indiana, por meio da organização social, econômica e cultural das unidades produtivas familiares. O estudo pretende enfocar o período que se estende entre a década de 1970 até o início do século XXI (2005). Além disso, buscou-se: identificar o perfil dos produtores familiares, compreender a organização interna e o estabelecimento de relações externas às unidades produtivas, analisar a importância das diferentes fontes de renda e caracterizar o desenvolvimento de estratégias de reprodução social dos produtores familiares. Desse modo, o trabalho encontra-se estruturado em quatro capítulos. No primeiro capítulo apresenta-se a fundamentação teórica e metodológica sobre a produção familiar e as estratégias de reprodução social. Também é enfocada a pluriatividade, na qual se privilegia a tentativa de definição da noção e os significados para a produção familiar do conjunto de atividades agrícolas ou não, realizadas dentro e fora da unidade produtiva, pelos membros das famílias rurais para a reprodução social no campo.

This work has like objective purpose to analyse the dynamics of familiar production in the Indiana city, by social, economic and cultural organization of familiars productives units. The study pretends to emphasize period that extends between decade 1970 until beginning of century XXI (2005). Besides, searched for: identify the profile of familiars producers, to understand the internal organization and establishment of external relationship ace productives units, to analyse the importance of differents income’s source and characterize the development of strategies social reproduction of the producer familiars. This way, the work is structured in four chapters. In first chapter shows the theoretical and methodologyc foundation about familiar production and strategies of social reproduction. Also is focalize the diversity activities, which each other privileges the experiment of definition in the notion and signification for the familiar production of group of rural activities or no, realized into and out in the productive unity by members of rural families for the social reproduction in the camp. In the second chapter discusses the formation and occupation of Indiana’s city in the context of Geografic Microrregião from Presidente Prudente. Is realized the characterization how it’s of point of view from District, the articulations of familiar production with the various instances from local power. In the third chapter look up to present agrarian structure in the Indiana’s city, by analyse of dice and information in the animal husbandry census of IBGE (1970-1995/96). The fourth chapter shows the results of the research about field realized in the units familiars productive of rural space in the Indiana city.
Keywords: Geografia; Estrategia; Pluriatividade; Reprodução social; Social reproduction - Strategy